2009
DOI: 10.3800/pbr.4.147
|View full text |Cite
|
Sign up to set email alerts
|

Role of interference from Daphnia and predation by cyclopoid copepods in zooplankton community structure: experimental analysis using mesocosms

Abstract: Abstract:The reduction of planktivorous fish populations in lakes through biomanipulation often results in increased abundance of the large cladoceran Daphnia and invertebrate predators, such as cyclopoid copepods, and also in decreased numbers of small zooplankters, such as the cladoceran Bosmina longirostris and rotifers. To investigate the factors causing reduced abundance of small zooplankton species in lakes, we performed a mesocosm experiment where the abundance of Daphnia and cyclopoid copepods (Mesocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In contrast to cladocerans and calanoids, cyclopoid copepods displayed greater mean abundance but no difference in mean length between fish-bearing (stocked and unstocked) and fishless lakes, resulting in greater cyclopoid biomass in the fish-bearing lakes. Unlike the cladoceran and calanoid species found in our study lakes, the cyclopoids (Mesocyclops edax/leukarti and Cyclops bicuspidatus thomasi) are relatively small as adults, which should reduce predation by fish (Kerfoot 1980;Ha and Hanazato 2009). In addition, cyclopoids are strong swimmers compared to cladocerans and calanoids, and thus more efficient at evading fish predation (Thorp and Covich 1991).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast to cladocerans and calanoids, cyclopoid copepods displayed greater mean abundance but no difference in mean length between fish-bearing (stocked and unstocked) and fishless lakes, resulting in greater cyclopoid biomass in the fish-bearing lakes. Unlike the cladoceran and calanoid species found in our study lakes, the cyclopoids (Mesocyclops edax/leukarti and Cyclops bicuspidatus thomasi) are relatively small as adults, which should reduce predation by fish (Kerfoot 1980;Ha and Hanazato 2009). In addition, cyclopoids are strong swimmers compared to cladocerans and calanoids, and thus more efficient at evading fish predation (Thorp and Covich 1991).…”
Section: Discussionmentioning
confidence: 89%
“…, and (iii) shifting the size structure of cladocerans towards a dominance of small taxa, e.g., Bosmina, which are common prey of cyclopoids (Kerfoot 1980;Ha and Hanazato 2009). An abundance of smaller cladocerans in fish-bearing lakes should increase survival and reproduction of adult cyclopoids (Williamson and Butler 1986;Hansen and Santer 1995;Hopp et al 1997) and developmental rates and survival of their nauplii and copepodites (Hopp and Maier 2005).…”
Section: R a F T 2003)mentioning
confidence: 99%
“…6). [16][17][18][19][20][21][22] The population increase of rotifera, which would be a typical indirect effect caused by the depletion of competitors (e.g., cladocera) [29][30][31] and lower sensitivity to toxicants than those of others (cladocera, copepoda, and ostracoda), had been similarly confirmed in most of the SMA outdoor studies.…”
Section: Direct and Indirect Effects And Recovery Potentialmentioning
confidence: 86%
“…12) However, although our synthetic 5 L microcosm was at the lower end of the range above, it visually showed sufficient stability and reproducibility of plankton populations to evaluate pesticide effects over a few months. Ostracoda and rotifera are considered to be important taxa in a microcosm for precise community evaluation; however, lack of or poor abundance of ostracoda taxa 29,[37][38][39][40][41][42] has often been observed in comparison with other taxa (cladocera 43,44) or rotifera 45) ) in indoor microcosms using natural zooplankton. In fact, rotifera frequently play a unique role in ecological adaptation via indirect population increase, as shown in Fig.…”
Section: Utility Of the Synthetic Model Ecosystemmentioning
confidence: 99%
“…Therefore, we concluded that the decline in small-bodied Daphnia was not related to fish introduction to the lake but rather caused by an increase in lake productivity and stronger food competition from large-bodied grazers. Another possible reason for the Daphnia longispina group decline could be pressure from invertebrate predators, which selectively eliminated smaller zooplankton (Ha and Hanazato 2009). Although WSP is a fishless lake, an increase in trophic status was also observed there.…”
Section: Decreases In the Dmentioning
confidence: 99%